ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PEMBIAYAAN MURABAHAH PT PERMODALAN NASIONAL MADANI MEKAAR SYARIAH KABUPATEN GOWA - Mildawati; Hadi Daeng Mapuna (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2023)
Abstract This research is a field research conducted by the author in Borong Pa'la'la Village, Pattallassang District, Gowa Regency with the title "Analysis of Sharia Economic Law on Murabahah Financing of PT PNM Mekaar Syariah in Borong Pa'la'la Village, Pattallassang District, Gowa Regency. This study aims to answer the questions: 1) What are the Sharia Economic Law Provisions on Murabaha Financing? 2) How is the Murabahah Financing Practice of PT PNM Mekaar Syariah in Borong Pa'la'la Village, Pattallassang District, Gowa Regency?. The method used in this research is descriptive analysis method (qualitative approach). There are two sources of data used in this study, namely, primary and secondary data sources. Meanwhile, the data collection technique in this research is using the interview and documentation method. The results of this study indicate that, Murabahah Financing at PT PNM Mekaar Syariah is a sale and purchase agreement between Mekaar Syariah or financing with customers. PT PNM Mekaar Syariah uses Murabahah contracts to carry out financing and wakalah contracts and wadiah contracts if needed, Mekaar Syariah gives money to the customer concerned at a determined price plus a profit margin agreed between Mekaar Syariah and the customer. Keywords: Capital Companies, Murabahah, Buying and Selling.